The psychometric properties test of the Malay version of the endometriosis health profile-30 - Mansor, Mardiana; Chong, Mei Chan; Chui, Ping Lei; Hamdan, Mukhri; Mustapa Kamal Basha, Muzaitul Akma (Saudi Arabian Armed Forces Hospital, 2023)
Abstract Objectives: To validate and determine the psychometric properties of the Malay version of the endometriosis health profile-30 (EHP-30) by confirmatory factor analysis.